2018
DOI: 10.1016/j.ultrasmedbio.2017.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Changes in Cervical Softness Using Shear Wave Speed in Early versus Late Pregnancy: An in Vivo Cross-Sectional Study

Abstract: The aim of this study was to assess the ability of shear wave elasticity imaging (SWEI) to detect changes in cervical softness between early and late pregnancy. Using a cross-sectional study design, shear wave speed (SWS) measurements were obtained from women in the first trimester (5-14 wk of gestation) and compared with estimates from a previous study of women at term (37-41 wk). Two sets of five SWS measurements were made using commercial SWEI applications on an ultrasound system equipped with a prototype c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 32 publications
13
22
0
1
Order By: Relevance
“…On the other hand, in the works of Muller et al and Hernandez-Andrade et al [38,39], although they obtained a narrower and smaller value range, they observed a similar trend; from the first weeks there is a notable decrease in the stiffness that in mid pregnancy softens. For its part, in a recent study of Carlson et al [40] using a prototype of shear waves, they noted that stiffness is reduced by half from the first to the third trimester, with values close to those of this work.…”
Section: + (4− 5) ⋅ ( )supporting
confidence: 85%
“…On the other hand, in the works of Muller et al and Hernandez-Andrade et al [38,39], although they obtained a narrower and smaller value range, they observed a similar trend; from the first weeks there is a notable decrease in the stiffness that in mid pregnancy softens. For its part, in a recent study of Carlson et al [40] using a prototype of shear waves, they noted that stiffness is reduced by half from the first to the third trimester, with values close to those of this work.…”
Section: + (4− 5) ⋅ ( )supporting
confidence: 85%
“…mean backscattered power difference, mBSPD) with actual tissue microstructure examined via nonlinear optical microscopy imaging in both Rhesus (Guerrero, 2018) and women (Guerrero et al, 2018b). Subsequently, we demonstrated in vivo with SWS that the cervix progressively softens as pregnancy advances in the Rhesus (Rosado-Mendez et al, 2017, 2018 and that the human cervix is significantly softer in late, as opposed to early, pregnancy (Carlson et al, 2015(Carlson et al, , 2018. The latter has been demonstrated by others as well (Muller et al, 2015).…”
Section: Discussionsupporting
confidence: 59%
“…In general, parameters which measure softness are based on propagation of shear waves (Carlson et al, 2014a(Carlson et al, ,b, 2015(Carlson et al, , 2018Huang et al, 2016;Hernandez-Andrade et al, 2013;Molina et al, 2012;Muller et al, 2015;Rosado-Mendez et al, 2017, 2018 and those which quantify microstructural organization are based on backscattered echo signals from the propagation of compressional waves (McFarlin et al, 2006(McFarlin et al, , 2010(McFarlin et al, , 2015aLabyed et al, 2011;Feltovich et al, 2010Feltovich et al, , 2012. Shear wave speed (SWS) estimation can quantify softness of the pregnant cervix in both women and Rhesus (Carlson et al, 2014a(Carlson et al, ,b, 2015(Carlson et al, , 2018Muller et al, 2015;Huang et al, 2016;Rosado-Mendez et al, 2017, 2018. Importantly, however, while SWS is a valuable biomarker of cervical remodeling, it provides no insight into why or how the tissue is becoming softer or more compliant (Feltovich and Hall, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Research moved towards looking for solutions, adopting the dynamic technique named shear wave elasticity imaging (SWEI) [51,240]. It has been widely used for the assessment of cervical changes [4,[241][242][243][244][245]. Carlson et al [4] measured SWS in human Ex vivo samples.…”
Section: Labor Disordersmentioning
confidence: 99%